"It Will Not Always Be This Way": Cognitive Alternatives Improve Self-Esteem in Contexts of Segregation. (March 2013) - Zhang, Airong; Jetten, Jolanda; Iyer, Aarti; Cui, Lijuan
In the context of school segregation in China, the authors propose that disadvantaged group members' self-esteem should improve when they consider the prospect of a better future for the group (i.e., awareness of cognitive alternatives to the lower status position). A pilot study established that country workers' children who were educated with city children (i.e., in integrated schools) reported higher self-esteem than country workers' children who were educated separately (i.e., in segregated schools). Study 1 showed that self-esteem among country workers' children was predicted by awareness of cognitive alternatives, but not by contact with city children. Study 2 experimentally manipulated cognitive alternatives, showing that self-esteem was enhanced when awareness of cognitive alternatives was high rather than low. Contact with city children again did not predict self-esteem. Findings demonstrate the importance of perceiving that social change is possible.